Promoting Students’ Mastery of Vocabulary in Descriptive Text through the Implementation of Semantic Mapping Strategy - Amira Wahyu Anditasari (Pascasarjana Universitas Negeri Makassar, 2022)
The students in SMPN 1 Nglames had difficulties memorizing English vocabularies and their meaning, and the problem affects their motivation to follow the class. Thus, implementing the right strategy to teach vocabulary is needed to address the issues. Previous studies affirmed that semantic mapping becomes an effective strategy for teaching vocabulary; it helps students memorize, understand, and use vocabulary more quickly. Therefore, this study aimed at implementing a semantic mapping strategy to improve the eighth graders' vocabulary mastery at SMPN 1 Nglames in the academic year of 2019/2020. Classroom Action Research consisting of four steps; planning, implementing, observing, and reflecting was used. The implementation was conducted in two cycles since the criteria of success have not been achieved yet in cycle one. In cycle one, there were only 68% of students gained ten points on their vocabulary scores and only 60% actively engaged. However, in cycle two it improved. 88% students gained ten points on their vocabulary score, and 73% students were actively engaged during the implementation of semantic mapping. Therefore, it can be concluded that semantic mapping successfully improved the students' mastery of vocabulary and increased their involvement.